Fructose-1, 6-bisphosphate promotes PI3K and glycolysis in T cells?. (August 2021) - Icard, Philippe; Alifano, Marco; Donnadieu, Emmanuel; Simula, Luca
Abstract : We propose that fructose-1, 6-bisphosphate (F-1, 6-BP) promotes a feedback loop between phosphofructokinase-1 (PFK1), phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt), and PFK2/PFKFB3, which enhances aerobic glycolysis and sustains effector T (Teff ) cell activation, while oxidative metabolism is concomitantly downregulated. This regulation, promoted by low citrate and mitochondrial ATP synthesis, also sustains the Warburg effect in cancer cells.